Cardiac Surgery in Birgunj: Early Experience - Ansari, Md. Afroz; Rana, Kush Bahadur; Shahi, Sanjiv Kumar (Med Phoenix, 2023)
Introduction: Cardio-vascular diseases are growing up in developing countries and they are the leading cause of deaths in the world, especially in low- and middle-income population. Various procedure were included such as open thoracotomy, CABG, Mitral valve repair aortic valve repair, however we aimed to study difficulties in performing cardiac surgery and complication related to cardiac surgery. Material & Methods: This retrospective study was carried out in Department of Surgery of National Medical College and Teaching Hospital, Birgunj, Parsa, Nepal. A total of 18 patients were included over period of 2019 to 2022 in this study. History and detailed clinical examination was performed as per the working proforma. Data analysis was done using SPSS (Statistical Package for social sciences), version 25. Result: Most of Coronary heart disease was seen in 40-59 years of age group with mean age of 48.2 years. A total of 83% patients were male. Triple vessel disease was the most common diagnosis (38.3% patients). Coronary artery bypass surgery (CABG) was most common surgery performed. 44.4% of patient develops complication out of which mortality occured in 11.11% of patient. Conclusion: To conclude, elective cardiac surgery is challenge in center like ours. Coronary heart disease (Triple vessels disease) was the most common indication of surgery.